Nesting ecology of the olive ridley sea turtle (lepidochelys olivacea) (cheloniidae) at el valle beach, northern pacific, colombia (2014)
The olive ridley (Lepidochelys olivacea) is the most common sea turtle to nest in Colombia. El Valle beach is considered the most important nesting beach for this species in South America. Intensive direct capture of nesting females and egg poaching for consumption and local commercial purposes has been a common practice for years. We conducted an analysis of the nesting ecology of the olive ridley on El Valle beach in the northern Pacific of Colombia in 2008. A total of 164 clutches were transferred to an artificial hatchery for protection. The peak of nesting occurred from the second half of August until the end of September, accounting for 64.6 % of all nests. Along the beach, the section most frequently used was Section 3, with 26 % of the nests. The nests were laid mainly in zone 3, 69%. We encountered 55 nesting females and marked 46 of them. Mean CCL was 64.9 ± 2.4 cm (± 1 SD) and mean CCW was 68.6 ± 2.6 cm. Females laid on average of 87.3 ± 14.2 eggs per clutch. We recorded two nesting events per female, with a mean inter-nesting period of 18.8 ± 4.2 days. The reproductive output for the season was 181.5 ± 34.8 eggs / female. Mean hatching success was 81.1 ± 12.1% and mean emergence success was 77.6 ± 12.7%. The incubation period was 65 ± 4.7 days. Our study is a valuable contribution to knowledge of the reproductive ecology of the olive ridley population regionally and globally.Ecología de anidación de la tortuga golfina (Lepidochelys olivacea) (Cheloniidae) en la Playa El Valle, Pacifico Norte, ColombiaEn Colombia, la tortuga golfina (Lepidochelys olivacea) es la más común de las tortugas anidantes. La playa El Valle es considerada la más importante para anidación en Suramérica. La intensa captura de hembras y saqueo de huevos para consumo y comercio local ha sido una práctica común por años. Realizamos un análisis de la ecología de anidación de la tortuga golfina en la Playa El Valle, Pacifico Norte, durante la temporada de 2008. Un total de 164 nidadas fueron transferidas a viveros de protección. El pico de anidación ocurrió durante la segunda quincena de agosto y septiembre con un 64,63 % de las posturas. A lo largo de la playa, el sector 3 presento la mayor frecuencia de anidación con 26 %. Los nidos fueron desovados principalmente en la zona 3, con 69 %. Encontramos 55 hembras y 46 fueron marcadas. El LCC fue (promedio± DE: 64,9 ± 2,4 cm) y ACC fue (promedio ± DE: 68,6 ± 2,6 cm). Las hembras desovaron 87,3 ± 14,2 huevos por nidada. Registramos dos eventos de anidación por hembra, con un intervalo de (promedio ± DE: 18,8 ± 4,2 dias). El producto reproductivo fue (promedio ± DE: 181,5 ± 34,8 huevos por hembra). El promedio en éxito de eclosión fue 81,1 ±12,1% y de emergencia 77,6 ±12,7%. El período de incubación fue (promedio ± DE: 65 ± 4,7 días). Nuestros datos son una  valiosa contribución al conocimiento de la ecología reproductiva de la población de tortugas golfina regional y globalmente.